The Role of Financing of Sharia Microfinance Institutions in Driving the Development of Small and Medium Industries - Nurfahmi Fadlillah; Jajang Hidayat (Jurnal Riset Akuntansi Soedirman, 2026)
Small and Medium Industries (IKM) play a strategic role in the national economy, yet continue to face structural barriers related to limited access to formal financing. This condition positions Islamic Microfinance Institutions (LKMS) as a viable alternative through the provision of sharia-based financing that is more inclusive and equitable. This study aims to analyze the influence of three LKMS financing scheme mudharabah, musyarakah, and murabahah on the development of IKM in Banyumas Regency. A quantitative approach with a causal design was employed, involving 35 IKM respondents selected through purposive sampling and analyzed using Partial Least Square Structural Equation Modeling (PLS-SEM) via SmartPLS. The outer model evaluation indicated that all outer loadings exceeded 0.70, with Average Variance Extracted (AVE) values ranging from 0.734 to 0.811 and Composite Reliability ranging from 0.892 to 0.945, confirming construct validity and reliability. The inner model results revealed that mudharabah exerted the most dominant effect (β = 0.415; p = 0.007), followed by musyarakah (β = 0.334; p = 0.050) and murabahah (β = 0.114; p = 0.042), with the model explaining 64.4% of the variance in IKM development (R² = 0.644). These findings suggest that LKMS should prioritize profit-and-loss sharing schemes while integrating digital services to expand inclusive financing outreach for small and medium enterprises.